Audit committee characteristics and firm performance: empirical evidence from listed diversified financial companies in sri lanka - Keerthana, G. (University of Jaffna, 2022)
Purpose:After the recent accounting scandals, the role of the audit committee has come under continuous scrutiny. This study explores the impact of audit committee characteristics on firm performance of listed diversified financial companies in Sri Lanka. Methodology: This study used 30 companies from the diversified financial sector listed in Colombo Stock Exchange. The quantitative method was employed and the data was gathered from the annual reports of listed companies from 2017 to 2021. Firm performance was measured using the ratios of Tobin's Q and ROE, while the audit committee size, audit committee independence, audit committee financial expertise and audit committee meetings were considered as proxies of audit committee characteristics. Furthermore, firm size and firm age were used as control variables for the study. Panel data regression analysis was employed to examine the hypotheses of the study. Findings: The results show that the audit committee expertise has a positive impact on Tobin's Q, which reveals that performance should be enhanced by more financial knowledge and abilities. Furthermore, Independent directors in the audit committee lead to the best firm performance measured by ROE. Independent directors reduce financial fraud, improve audit quality, as well as reduce agency problems and enhance the firm's performance. Other variables such as audit committee size and audit committee meetings have not shown any significant impact on firm performance. Research limitations: The study only examines diversified financial sector companies listed on the Colombo Stock Exchange from 2017 to 2021. Therefore, the Findings of this study cannot be generalized to all sectors of the Colombo Stock Exchange. Implications: The Findings would be helpful for financial sector companies to enhance the effectiveness of their audit committees and investors' confidence in their firm's performance. Moreover, it helps fill the exciting literature on audit committee characteristics and firm performance with new data. This paper will be greatly beneficial for financial practitioners and policymakers because it provides practical suggestions and recommendations about the types of external audits indispensable for the overall effectiveness and performance of firms. The study Findings may also aid strategic policy formulation and execution for better corporate governance practices for profit and wealth maximization.
Keywords: Audit committee financial expertise; Audit committee independence; Audit committee meetings; Tobin's Q